Art and Archaeology : collaborations, conversations, criticisms - Cochrane, Andrew; Russell, Ian Alden (One World Archaeology, 2014)
This volume presents a collection of collaborations and conversations between archaeological, contemporary art, and heritage practitioners. Departing from the proceedings of the Sixth World Archaeological Congress's 'Archaeologies of Art' theme and Ábhar agus Meon exhibitions, it includes papers by seminal figures as well as experimental work by those who are exploring the application of artistic methods and theories to the practice of archaeology. Art and Archaeology: Collaborations, Conversations, Criticisms encourages the creative interplay of various approaches to 'art' and 'archaeology' as contributions to how we interpret and understand the world. Established topics such as cave art, monumental architecture and land art will be discussed alongside treatments of modern and contemporary drawing, installation art, performance art, photography, sculpture, and video art. Here, the parallel roles of artists as makers of worlds and archaeologists as makers of pasts are brought together in an appreciation of human creativity.